Association between fear of childbirth and maternal acceptance of pregnancy - POTUR, DİLEK; DEMİRCİ, NURDAN (WILEY, 2017)
AimThis descriptive study aimed to explore the associations between fear of childbirth, acceptance of pregnancy and identification with the motherhood role among primipara women. BackgroundWomen who have difficulty accepting their pregnancy have a harder time adapting to pregnancy and motherhood and experience more fears related to childbirth. The number of studies conducted on this topic is limited. MethodsThis study involved 310 pregnant women admitted to a public hospital in Istanbul between January and June of 2013. A participant identification form, the Prenatal Self-Evaluation Questionnaire and the Wijma Delivery Expectancy/Experience Questionnaire Version A were used for data collection. ResultsPregnant women participating in the study experienced moderate levels fear of childbirth. Pregnant women who requested caesarean section experienced more intense fear of childbirth. Fear of childbirth scores had significant but weak correlations with acceptance of pregnancy and identification with the motherhood role. ConclusionThe findings showed that acceptance of pregnancy and identification with the motherhood role are weakly associated with fear of childbirth. Implications for nursing and health policyThe results from this study can be used to help: increase awareness among health professionals (doctors, nurses, midwives) in antenatal care services about a mother's adaptation to pregnancy and the negative effects of fear of childbirth; direct future research examining factors affecting adaptation to pregnancy and fear of childbirth; establish routine assessments for adaptation to pregnancy and fear of childbirth; provide professional support for women with difficulties adapting to pregnancy and with fear of childbirth; result in reduced complications from invasive methods such as caesarean section due to less requests for these procedures; and promote the health of mothers and babies.
Keywords: Acceptance of Pregnancy; Antenatal Period; Caesarean Section; Fear of Childbirth; Midwife; Motherhood Role; Nurse; Prenatal Care; Spontaneous Vaginal Delivery; Turkey; ANTENATAL EDUCATION; AUSTRALIAN WOMEN; BIRTH OUTCOMES; SELF-EFFICACY; ADAPTATION; DELIVERY; COHORT; AGE